Vortex structure and dynamics of Florida Keys waterspouts: 1974 field experiment, final report - Sinclair, P. C., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1974)
From direct penetrations of the waterspout funnel by specially instrumented aircraft, a quantitative description of the dynamic-thermodynamic structure of the waterspout has been developed. The Navier-Stokes equations of motion for the waterspout vortex are simplified by an extensive order of magnitude analysis of each term in the equations. The reduced set of equations provides a realistic mathematical model of the waterspout vortex. Further simplification shows that the cyclostrophic-Rankine combined vortex model accounts for, on the average, approximately 63% of the measured pressure drop from the environment to the waterspout core. The penetration measurements show that the waterspout funnel consists of a strong rotary and vertical field (radial component is smaller) of motion which results in a combined flow pattern similar to that of a helical vortex. In general, the measurements indicate that this one-cell vortex structure is the dominate configuration. However, several penetrations suggest reduced positive vertical velocities near the funnel core, and in one case, a downdraft core with vertical velocity of -0.8 msec-1. These measurements indicate that waterspout vortex may in some stages of development have a structure more closely described by the two-cell vortex such as discovered by Sinclair (1966, 1973) for the dust devil vortex. The temperature and pressure structure show that the waterspout, like the dust devil, is a warm core (ΔT = 0.1 to 0.5°C), low pressure (ΔP = -0.6 to -8.4 mb) vortex. All aircraft penetrations of the visible funnels were made within 150 m of cloud base at speeds of 55-65 msec-1.
Includes 2 different reprints of the article: Waterspout wind, temperature and pressure structure deduced from aircraft measurements by Verne H. Leverson and Peter C. Sinclair, Jospeh H. Golden.
Includes in its entirety Verne H. Leverson's M.S. thesis, "Waterspout structure and dynamics."
Keywords: Waterspouts -- Florida -- Florida Keys; Aeronautics in meteorology